Loads in the hip joint during physically demanding occupational tasks: A motion analysis study. Issue 12 (18th September 2015) - Varady, Patrick Aljoscha; Glitsch, Ulrich; Augat, Peter
Abstract: Epidemiologic studies of osteoarthritis of the hip indicate a possible connection between work related activities and the pathogenesis of the disease. This study investigated the hip joint contact forces for physically demanding occupational tasks (lifting, carrying, transferring of a weight (mass: 25 kg, 40 kg and 50 kg); stair climbing without and with additional load of 25 kg; ladder climbing) and compared these with everyday activities (level gait, sitting down and getting up). The hip joint contact force was calculated with the human multibody simulation software AnyBody employing motion capture and ground reaction force measurements by force plates and an instrumented staircase and ladder. Although the results for 11 male test subjects showed individual variations, a general trend could be observed in regards of force curves' characteristics and maxima. The largest joint contact forces calculated were (637±148)%-body weight for horizontal transfer of a 50 kg weight. For several of the occupational activities the computed hip joint contact forces were significantly larger compared to the investigated examples of activities of daily living. This study provides original data of simulated hip joint contact forces for physically demanding activities.